2010
DOI: 10.1002/ijc.25135
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B is expressed in urothelial carcinoma and promotes cancer cell invasion

Abstract: Granzyme B (GrB) is a serine proteinase known to be expressed by cytotoxic lymphocytes and to induce, in presence of perforin (Pf), apoptosis in target cells. Recently, GrB expression has been shown (often in absence of Pf) in nonlymphoid cells, but its function is not defined. In our study, we investigated GrB and Pf expression in bladder cancer cell lines and in urothelial carcinoma (UC) tissues by reverse transcription-polymerase chain reaction (RT-PCR), Western blot, ELISA, immunofluorescence and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 50 publications
3
58
0
1
Order By: Relevance
“…These substrates include extracellular matrix (ECM) proteins such as vitronectin, laminin, fibronectin, decorin, and biglycan [57]. Cleavage of these proteins by GzB has been implicated in detaching adherent cells bound to these proteins [5], promoting the migration of cells through matrigel [6], and releasing matrix-bound cytokines [7]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These substrates include extracellular matrix (ECM) proteins such as vitronectin, laminin, fibronectin, decorin, and biglycan [57]. Cleavage of these proteins by GzB has been implicated in detaching adherent cells bound to these proteins [5], promoting the migration of cells through matrigel [6], and releasing matrix-bound cytokines [7]. …”
Section: Introductionmentioning
confidence: 99%
“…GzB expression can also be found in cell lines and/or primary tumours of non-lymphoid origin including acute myeloid leukemia [17], prostate cancer [18] and some carcinomas of the breast [19] and urothelium [6]. While the significance, if any, of GzB expression in most of these malignancies has yet to be firmly established, in urothelial carcinoma GzB expression correlates with increased invasiveness and epithelial-to-mesenchymal transition of tumour cells [6]. More importantly, this study demonstrated that in GzB-expressing bladder cancer cell lines, GzB promotes the invasion of these cells through matrigel, presumably through the degradation of ECM proteins within the matrigel [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the wild-type QPY allele of GZMB gene encoding GrB preproprotein with Gln 48 , Pro 90 , and Tyr 247 in its sequence, the RAH allele of GZMB gene encodes GrB preproprotein containing Arg 48 , Ala 90 , and His 247 (67). The RAH allele occurs at a frequency rate of 25-30% in each of the racial groups studied and it was proven to represent a neutral GZMB gene polymorphism (68).…”
Section: Granzyme B Gene Organization and Regulation Of Expressionmentioning
confidence: 99%
“…Interestingly, GrB has been detected in cancer cells of primary human breast carcinomas (88,89), lung carcinomas (88), urothelial carcinomas (90) and in nasal-type NK/T-cell lymphoma (91). Recently, GrB expression was revealed by immunohistochemistry in oral squamous cell carcinoma and it seems to be localized also in cancer cells (92).…”
Section: Granzyme B Gene Organization and Regulation Of Expressionmentioning
confidence: 99%